Utilización de cultivos hidropónicos a base de lenteja (Lens culinaris) y arveja (Pisum sativum) en la alimentación de codornices (Coturnix coturnix) en la etapa de crecimiento-engorde - Sánchez García, Karen Gabriela (2024)
The research was carried out in the Coast region of Ecuador, in the Quail Seedbed Project promoted by the Research Department of the Technical University of Babahoyo, located at km 7 ½ of the Babahoyo-Montalvo Road in the Province of Los Ríos. The study site is characterized by an average annual temperature of 25.7 °C. The topic developed in this research was the use of hydroponic crops based on lentils (Lens culinaris) and peas (Pisum sativum) in the feeding of quails (Coturnix coturnix) in the growth-fattening stage. The variables analyzed were weekly body weight (g), feed consumption (g), feed conversion (g), carcass yield (%), and mortality (%). Two treatments with three repetitions were used versus a control treatment giving 9 experimental units, with 10 animals per experimental unit with a total of 90 animals. The same ones were distributed under a Completely Randomized Design (DCA). The experimental results obtained were subjected to a comparison of measurements according to Tukey at significance levels (P > 0.05), and finally the Benefit/Cost Ratio was used to determine the profitability of the treatments. Regarding the variables analyzed in the study, the treatment with the best feed conversion was obtained in T0 with 2.53 (g) with significant statistical differences according to the Tukey test (P> 0.05), compared to T1 with 3.11 g and T2 with 3.08. The weight variable did not present significant statistical differences between treatments, however numerically in the final week, it is observed that T2 179.00 g has the highest average weight, followed by T1 178.33 g and T0 166.33 g. On the other hand, in the variable feed consumption according to the Tukey test (P > 0.05) there was a significant statistical difference between the treatments where T0 with 2.53 g consistently presents the lowest values of feed conversion. While T1 with 3.11 g and T2 with 3.08 show higher values of feed conversion. The highest average yield percentage was observed in T0 with 74.26 %, followed closely by T2 74.11 %, on the other hand the lowest yield was observed in T1 with a value of 72.93 %. The mortality rate registers for T0 the highest number of deaths with 4 deaths, followed by T1 which registered only one death, unlike T2 which recognized 2 deaths. It should be noted that in Benefit/Cost T0 registers 1.91 USD, compared to the other treatments T1 (1.44 USD) and T2 (1.40 USD).